Infancy‐onset diabetes caused by de‐regulated AMPylation of the human endoplasmic reticulum chaperone BiP. Issue 3 (27th January 2023) - Perera, Luke A; Hattersley, Andrew T; Harding, Heather P; Wakeling, Matthew N; Flanagan, Sarah E; Mohsina, Ibrahim; Raza, Jamal; Gardham, Alice; Ron, David; De Franco, Elisa
Abstract: Dysfunction of the endoplasmic reticulum (ER) in insulin‐producing beta cells results in cell loss and diabetes mellitus. Here we report on five individuals from three different consanguineous families with infancy‐onset diabetes mellitus and severe neurodevelopmental delay caused by a homozygous p.(Arg371Ser) mutation in FICD . The FICD gene encodes a bifunctional Fic domain‐containing enzyme that regulates the ER Hsp70 chaperone, BiP, via catalysis of two antagonistic reactions: inhibitory AMPylation and stimulatory deAMPylation of BiP. Arg371 is a conserved residue in the Fic domain active site. The FICD R371S mutation partially compromises BiP AMPylation in vitro but eliminates all detectable deAMPylation activity. Overexpression of FICD R371S or knock‐in of the mutation at the FICD locus of stressed CHO cells results in inappropriately elevated levels of AMPylated BiP and compromised secretion. These findings, guided by human genetics, highlight the destructive consequences of de‐regulated BiP AMPylation and raise the prospect of tuning FICD's antagonistic activities towards therapeutic ends. Synopsis: Modification of the endoplasmic reticulum (ER) chaperone BiP by FICD, an enzyme that adds or removes an adenosine monophosphate (AMP), regulates protein folding homeostasis. Secretory cells that produce the hormone insulin or promote neurodevelopment depend on intact ER function. Homozygosity of an Arg371Ser mutation in FICD causes infancy‐onset diabetes mellitus and neurodevelopmental delay. The Arg371Ser corrupts FICD by inactivating its ability to remove AMP from BiP. Inappropriately, elevated levels of AMPylated BiP interfere with secretion, suggesting a molecular mechanism for this genetic disorder. Abstract : Modification of the endoplasmic reticulum (ER) chaperone BiP by FICD, an enzyme that adds or removes an adenosine monophosphate (AMP), regulates protein folding homeostasis. Secretory cells that produce the hormone insulin or promote neurodevelopment depend on intact ER function.